Gestão internacional de pessoas – os desafios da área de recursos humanos na gestão de expatriados: uma análise no segmento de tecnologia da informação - Meier, Valencia Cristina (Universidade do Vale do Rio dos Sinos, 2013)
This work is a parallel study which lies in the fie ld of international management of Human Resources. The objective of this research is to identify and analyze the main challenges in the area of Human Resources by supporting the process of managing expatriate professionals in Information Technology multinational Having specific objectives, the research aims to understand the role of Human Resources in the expatriation process, discuss the coordination of actions between the HR and the organizational leaders and finally point out the contributions to the establishment of HR policies that subsidize improvements in the management of expatriation processes in organization objects of this study. The methodology used was a qualitative approach, as well as exploratory through interviews with expatriate, managers and HR professionals who work in the organizations surveyed. We also used a focus group with experts in expatriation to give greater consistency to the research and with the aim of increasing the understanding of different perceptions and bring other answers regarding the researched topic. The categorical analysis was used as a method of content analysis to the interviews. The main findings in the study show that there was a convergence between the companies surveyed regarding the need to seek a Human Resources area with more strategic operation as well as the consolidation of an expatriation policy, which takes into account from the selection to the repatriation of professionals. Another significant result concerns the need to properly prepare local managers who will monitor the expatriate and finally, the companies that make up the sample adopt the policies and practices of Human Resources presented, but those relating to the selection, training and repatriation seem to depend much more on the action from the matrix than shares local HR. The demand for HR comes through the need for a more agile and able to develop global capabilities that continuously move talents around the world and act strategically to add value to organizations.
Keywords: Gestão estratégica de pessoas; Gestão internacional de recursos humanos; Internacionalização; Expatriação; ACCNPQ::Ciências Sociais Aplicadas::Administração